Predictive factors for failure of endoscopic management therapy in peptic ulcer bleeding - Siva Radhakrishnan; Al Zubaidi Ghazi; Masoud Al Kashoob; Nihar Mohan (The Saudi Journal of Gastroenterology, 2002)
Background: After endoscopic therapy for peptic ulcer bleeding, rebleeding occurs in up to 20% of patients. Objective: The aim of this retrospective analysis was to identify the factors responsible for failure to achieve hemostasis or rebleeding after endoscopic therapy. Methods: Seventy six patients who bled from peptic ulcers and received endoscopic therapy were identified in a retrospective analysis of six years, from 1993 to 1998, in a tertiary care hospital in Muscat, Oman. All patients were endoscoped within 24 hours and received endoscopic treatment, either injection of 1/10,000 adrenaline alone or both injection and thermocoagulation. We looked at the following factors, which could have influenced the outcome of endoscopic therapy. The clinical and endoscopic parameters used to assess the outcome of endoscopic therapy were: age, sex, blood pressure and hemoglobin on admission, number of units of blood transfused , use of NSAID, comorbid conditions, ulcer site, ulcer size. Forrest grade, injection alone and injection plus thermocoagulation. Results: Endoscopic therapy failed in 16 patients (21%). Twelve patients received a second endoscopic treatment , but 13 patients eventually required surgery. Six patients died as a result of bleeding (mortality 8%). Among the parameters, hemoglobin on admission, more than six units of blood transfusion, shock, co-morbid diseases, ulcer site and size and Forrest grade la predicted the possibility of failure of endoscopic therapy. Conclusion: In patients presenting with peptic ulcer bleeding, hemoglobin less than 10 grams, more than six units of blood transfusion, shock on admission, co-morbid disease, posterior wall duodenal ulcer, large ulcer size of > I cm size and Forrest la predicted failure of endoscopic therapy.